En-bloc kidney transplants from very small pediatric donors: a propensity score matched analysis - Silvia Oberparleiter; Felix J. Krendl; Thomas Resch; Rupert Oberhuber; Hannah Esser; Florian Ponholzer; Annemarie Weissenbacher; Robert Breitkopf; Hannes Neuwirt; Stefan Schneeberger; Manuel Maglione; Benno Cardini (Frontiers in Pediatrics)
BackgroundKidneys from brain-death small pediatric donors ≤2 years are still classified as marginal organs. Herein, we analyse the outcomes following en-bloc kidney transplantation (EBKT) from pediatric donors ≤2 years into adult recipients compared to standard criteria donor kidney transplant recipients (SKTs).MethodsA retrospective single center analysis of a prospectively collected and auditable database identified six EBKTs and 75 SKTs between January 2015 and June 2017. Propensity score matching minimized selection bias.ResultsAfter a median follow-up of 74 months, five-year patient and graft survival were 100%, each in the EBKTs group. Following SKTs, the five-year patient survival rate was 94.7%, likewise death-censored graft survival reached 94.7%. Two EBKT cases experienced unilateral arterial graft thrombosis requiring unilateral nephrectomy, with full recovery and good kidney function. At hospital discharge, recipients of EBKTs showed decreased eGFR compared to SKTs, however, from 3 months onward this reversed and following a median follow-up of 74 months the median eGFR was twice as high after EBKT compared to SKT (107 ml/min/1.73m2 vs. 52 ml/min/1.73m2, p < 0.001). These favourable results persist in the PSM analysis.ConclusionEBKTs from very small pediatric donors show excellent long-term kidney function. The higher incidence of postoperative complications does not translate into poorer mid-term patient and graft survival.